Management of Femoral Vessel Injuries: A 6-year Single-center Experience. Issue 1 (January 2015) - Sciarretta, Jason D.; Macedo, Francisco Igor B.; Ebler, David J.; Ruiz, Gabriel; Otero, Christian A.; Pizano, Louis R.; Namias, Nicholas
Femoral vessel injuries are a familiar injury treated in busy urban trauma centers. The majority of peripheral vascular injuries to the lower extremity occur most commonly to the femoral vessels. The increasing incidence of civilian violence provides an opportunity to perform a comprehensive review and management of these injuries.